Foreign experience training social workers - Кравченко, О. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
In the article the content of the training of social workers in the Nordic countries with distinguishing general recommendations for national social education. Established that an important aspect of higher education in Sweden, the Netherlands, Finland is the principle of "academic freedom" which has 4 statuses: University of freedom in determining the content of curricula and educational programs; freedom of the faculty of determining the content of courses; Freedom teacher of determining the content of his course; student freedom in the choice of subjects and specialization.